mproving Science Communication Skills Using Worksheets Based on Think-Talk-Write - Fadly, Wirawan; Andaria, Meri (UIN Fatmawati Sukarno Bengkulu, 2021)
Science communication skills are the process of conveying information or data from observations orexperimental results to be known and understood by others. Student worksheets are printed teachingmaterials in the form of guides for carrying out an investigation or problem-solving activities concerningthe basic competencies that must be achieved and are intended to streamline learning and help studentsmaster understanding, skills, and attitudes. Student worksheets developed in this study think talk write(TTW) based student worksheets. This study aims to determine the effectiveness of TTW-based studentworksheets in improving science communication skills. The research method used was an experimentaldesign with a randomized control group pre-test post-test. Data collection was done by giving 18 items ofpre-test and post-test. Data analysis was performed using the N-Gain test and one-tailed t-test. Based onthe results of this study, it was found that an increase in the results of the N-Gain test was 58.68%, whilethe results of the one-tailed t-test showed that the TTW-based student worksheets could help studentsimprove their science communication skills